Distribution of n‐alkan‐2‐ones in Qionghai Lake sediments, southwest China, and its potential for late Quaternary paleoclimate reconstruction. (2nd February 2021) - Wang, Gen; Wang, Yongli; Wei, Zhifu; He, Wei; Zhang, Ting; Ma, Xueyun; Yu, Xiaoli
Abstract: Studies on long‐chain n ‐alkan‐2‐ones from lake sediments remain sparse. In this study, we present an n ‐alkan‐2‐one record from Qionghai Lake, southwest China, to assess the paleoclimate significance of variations in their compositions. A homologous series of n ‐alkan‐2‐ones ranging from C21 to C35 were identified, with maximum concentrations of the C29 or C31 chain lengths and a strong odd‐over‐even predominance. This type of n ‐alkan‐2‐one is considered to derive mainly from microbial oxidation of the corresponding n ‐alkanes, and partial inputs from plants. The n ‐alkan‐2‐one‐derived average chain length (ACL) and carbon preference index (CPI) values changed significantly over the past 28k cal a bp, consistent with the sediment grain size and n ‐alkane proxies from the same core. Generally, the high CPI27‐33 ‐ket and low ACL27‐33 ‐ket values indicated cold and dry climates such as for the Last Glacial Maximum (23.2–19.7k cal a bp ), Heinrich 1 event (17.6–15.6k cal a bp ) and Younger Dryas (12.8–11.6k cal a bp ), but low CPI27‐33 ‐ket and high ACL27‐33 ‐ket values denoted a warm and humid Holocene Climatic Optimum (7.0–4.3k cal a bp ). Therefore, n ‐alkan‐2‐ones have great paleoclimatic potential and can be applied together with other biomarkers to reconstruct a reliable paleoclimate record in lake sediments.